من ناحية المادة الدراسيةـ MTsS Darul Ulum Banda Aceh تدريس النحو بـــــ - Salsabila, Cut Nadia; Mahmud, Salami; Fajriah, Fajriah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
Based on the results of the  researcher’s observation on the first grade students at MTsS Darul Ulum Banda Aceh, Not all of  the students  understand the material mubtada’ khabar well. This is because the teacher only uses one book teaching. Therefore, researcher are interested in developing Arabic teaching material  mubtada' khabar. The purposes of this study were to determine the steps in developing teaching material, to determine students’ responses to teaching the developed material. And to determine the achievement of the teaching materials. The researcher  used   the Research and Development method, using the ADDIE model. The instrument used an expert validation sheet and student response questionnaire. The samples of this research are 20 male students from Class VII/I. The results of this research are: 1) The steps in the development of teaching materials consist of analysis,  design,  development, implementation, and  evaluation. 2)Teaching materials can be used after an assessment by experts, the results from material experts are  75% in the category (worthy), the results from design experts are 95% in the category (very worthy), the results from Arabic teacher experts are 85% in the category (very worthy). 3) The results of students’ responses to the teaching materials developed on  mubtada’  khabar  were positive in grade    94,5%  (stronly agree).